Simulation of riser size from musty zone of unrisered Alsi7mg alloy (2007)
Solidification simulation packages incorporate risers in their Finite Element meshing programs. The placement of the risers is normally juggled in different positions until the best positions are obtained. Also riser sizes are also determined based on riser size calculations. This work has narrowed down position options by first simulating unrisered castings of an AlSi7Mg alloy. Using the location of the mushy zone and the size of the zone, appropriate size and locations were determined for the riser thus limiting the number of trial and error simulation runs. Using the size and locations of mushy zone it has been discovered that risers of equivalent lineal size should be placed in the locations of these mushy-zones. Simulations were done using a rectangular block and a gas burner.